MEMBUAT FEEDS SOSIAL MEDIA INSTAGRAM SEBAGAI SALAH SATU MEDIA PROMOSI WISATA AGRO LEMBAH KECUBUNG: CREATING INSTAGRAM SOCIAL MEDIA FEEDS AS ONE OF THE MEDIA FOR WISATA AGRO LEMBAH KECUBUNG PROMOTION - Lutvia Febrin Sholekhaningtyas; Restu Ismoyo Aji (Pakis Journal Institute, 2023)
Wisata Agro Lembah Kecubung is the first natural tourist destination in Penanggungan Village, Trawas District, Mojokerto Regency. Lembah Kecubung is taken from the name of a spring which is a resource for the surrounding community. Wisata Agro Lembah Kecubung itself has the theme